Analisis Bibliometrik Penelitian Pendidikan Akidah Akhlak pada Database Dimensions - Charitsatun Najah; Busro Busro (UIN Sunan Gunung Djati Bandung, 2023)
Akidah Akhlak education is an education that is very important for society or today’s youth, Akidah and Akhlak are one of the foundations of the Islamic religion whose scope of teachings is also large. This study aims to try to answer the deficiencies and complement the studies in previous literature studies, the method used in this research is to use the bibliometric method. In this study a lot of data was found regarding Akidah Akhlak Education, based on data obtained by Akidah Akhlak Education in the dominant research category in the field of education, the researcher who published the most research on Akidah Akhlak Education was Dedy Wahyudi, and the place of publication was dominated by the Journal of Islamic Education Indonesian.